Implementation of Learning Methods Based on Natural Materials and Science for Group B Kindergarten - Hartin Kurniawati; Ihda Husnayain Madani (Universitas Islam negeri Mahmud Yunus Batusangkar, 2024)
The purpose of this research is to determine the application of the learning modelof natural materials and science centers for group B students in LestariKindergartens and to find out the supporting and inhibiting factors in theapplication of the learning model of natural materials and science centers inLestari Kindergartens. This research uses a qualitative approach that aims todescribe the processes that occur in the field. Data collection techniques arecarried out through observation, interviews, and documentation. The resulting datais then analyzed, through data reduction, data presentation, and conclusions usingqualitative descriptive analysis. The research results show: (1) The application ofnatural materials and science center learning includes: planning, implementationand evaluation. The implementation of central learning uses four steps startingfrom the playing environment, the steps before playing, the steps during play, andthe steps after playing. Evaluation of learning centers is carried out by observationand then assessed using checklists and anecdotes, as well as documentation in theform of work results. (2) Supporting factors in the application of natural materialsand science centers to science abilities, namely, the teacher's ability to masteradequate learning materials and learning media, while inhibiting factors in theapplication of natural materials and science centers to students' science abilities,namely: changing the K13 curriculum to a curriculum freedom to learn, facilitiesand infrastructure and children's activeness in participating in learning activities.Keywords: Learning Center Model, Natural Materials and Science Center, Child.